(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This study investigated the vegetation characteristics and floristic diversity along the coastal area of Wadi Al-Sahl in the northwestern part of Tobruk City, covering a designated area. A comprehensive survey recorded 66 plant species, belonging to 58 genera across 23 families. The family Asteraceae ranked first with 15 species and 15 genera, followed by Chenopodiaceae with 12 species and 7 genera. In terms of frequency, Atriplex halimus exhibited the highest frequency (50%) and a relative frequency of 11.36%. Concerning density, Echium angustifolium was the highest with 43 individuals and a relative density of 15.30%, followed by Polygonum equisetiformis (33 individuals, 11.74% relative density). Biodiversity indices calculated based on 281 individuals from 27 species showed a moderate to high species diversity, with the Shannon–Wiener index (H’) at 2.81. Simpson’s dominance index (D) was low (0.079), and Pielou’s evenness (J) was high (0.85), indicating low dominance and high distribution evenness. These results confirm a rich plant community well-adapted to the semi-arid coastal environment of Wadi Al-Sahl.